APAKAH BIMBINGAN KELOMPOK DENGAN VIDEO MODELING KESENIAN TUNDANG EFEKTIF MENINGKATKAN KETERBUKAAN DIRI? - Amallia Putri; Halida halida; Jagad aditya dewantara; Kornelia Tantri Yulia; Herlinda Herlinda; Yulia Ningsih; Risa Ardiyanti (Jurnal Education and Development, 2023)
This study aims to determine the effectiveness of group guidance with video modeling of tundang art to increase students' self-disclosure. This type of research is pre experimental design, with a one group posttest design model. The population in this study is the seventh grade students of SMPN in Pontianak City as many as 49 people. The sampling technique was done by using random sampling technique. The method of data collection is using a questionnaire. The data used are interval data, the analysis is carried out through parametric statistics and hypothesis testing using paired sample t-test. The results showed that the average pretest result was 141.98 and the posttest was 148.94, the average before and after being given treatment was -6.959 this means that students' self-disclosure has increased. It is known that sig (2-tailed) 0,000 < 0.05 data indicates the alternative hypothesis (Ha) is accepted. The composition of the tundang art arrays which are arranged using the A-A-A-A pattern accompanied by Malay music containing moral messages and the values ​​of self-disclosure are able to influence the way students think and behavior. Another finding from this research is that the crooked and distinctive Malay accent of the rhyme speakers and the melodic voice contribute to changes in students' thoughts and behavior. It can be concluded that group guidance with video modeling of tundang art is effective in increasing self-disclosure of junior high school students in Pontianak City.